Antibiotic Resistant Bacterial Isolates from Captive Green Turtles and In Vitro Sensitivity to Bacteriophages. (24th September 2017) - Delli Paoli Carini, Alessandro; Ariel, Ellen; Picard, Jacqueline; Elliott, Lisa
Abstract : This study aimed to test multidrug resistant isolates from hospitalised green turtles (Chelonia mydas) and their environment in North Queensland, Australia, for in vitro susceptibility to bacteriophages. Seventy-one Gram-negative bacteria were isolated from green turtle eye swabs and water samples. Broth microdilution tests were used to determine antibiotic susceptibility. All isolates were resistant to at least two antibiotics, with 24% being resistant to seven of the eight antibiotics. Highest resistance rates were detected to enrofloxacin (77%) and ampicillin (69.2%). More than 50% resistance was also found to amoxicillin/clavulanic acid (62.5%), ceftiofur (53.8%), and erythromycin (53.3%). All the enriched phage filtrate mixtures resulted in the lysis of one or more of the multidrug resistant bacteria, including Vibrio harveyi and V. parahaemolyticus . These results indicate that antibiotic resistance is common in Gram-negative bacteria isolated from hospitalised sea turtles and their marine environment in North Queensland, supporting global concern over the rapid evolution of multidrug resistant genes in the environment. Using virulent bacteriophages as antibiotic alternatives would not only be beneficial to turtle health but also prevent further addition of multidrug resistant genes to coastal waters.